2021
DOI: 10.51470/plantarchives.2021.v21.no2.046
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobials Use in Broiler Chicken Breeding: Case of the Ain Defla Province (Algeria)

Abstract: The objective of this study is to assess the use of antimicrobials in the broiler production in Algeria, through a survey completed by private veterinarians of the Ain Defla province. In this context, 65 band breeding were studied for antimicrobial use between October 2019 and June 2020. The results showed that all of the studied bands received antimicrobial treatments for at least 5 days during the breeding period. Quinolones class was the most widely used class of antimicrobials (24.4%), followed by the tetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…These results are consistent with those reported in Algeria by Mokhtar Rahmani et al [27] and with those reported in Morroco by Chaiba et al…”
Section: Nature Of the Antibiotic Residue Detected In The Contaminate...supporting
confidence: 93%
See 1 more Smart Citation
“…These results are consistent with those reported in Algeria by Mokhtar Rahmani et al [27] and with those reported in Morroco by Chaiba et al…”
Section: Nature Of the Antibiotic Residue Detected In The Contaminate...supporting
confidence: 93%
“…The liver is considered a palatable offal with known benefits for the body. In Iran, the liver is traditionally the most consumed offal and is considered a quality source of protein [19,27]. The liver is rich in vitamins A, B, and D [28] and contains minerals and trace elements such as iron and zinc [14].…”
Section: Motivations To Consume Each Type Of Offal (Liver Gizzard And...mentioning
confidence: 99%
“…The results showed that the absolute abundance of most ARGs in the vermicompost products was reduced to different degrees compared with that in the initial cow dung, indicating that earthworms had a reducing effect on some antibiotic resistance determinants, which is consistent with the results of Han et al [ 33 ]. Furthermore, sulfonamide resistance genes ( sul -ARGs) were most abundant in the initial substrate of cow dung, followed by tetracycline resistance genes ( tet -ARGs) ( Figure 4 ), which may be due to the widespread use of sulfonamides and tetracyclines in animal breeding [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, the authors of the article S.A. Mohammed, B.A.J. Ridha talk about the need to attract the attention of farmers to protecting the environment of rural areas from pollution [5]. A significant number of chemicals and fertilizers are used in agricultural production, the unsystematic use of which can significantly worsen the environmental situation in rural areas.…”
Section: Introductionmentioning
confidence: 99%